Strategi Bidang P3A DINSOSDALDUKKBP3A Kabupaten Purbalingga Dalam Menangani Kekerasan Pada Anak Melalui Sosialisasi Berbasis Sekolah - Kinanti, Andin; Suyuti, Muh Hikamudin (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
Social problems that now often occur have a negative impact on victims, perpetrators, and the environment. Such as child abuse which is currently a matter that needs to be considered, their age must be given knowledge and insight into the dangers of child abuse. The socialization of violence against children carried out by the P3A Division of DINSOSDALDUKKBP3A Purbalingga Regency is an effective step in preventing cases of violence that are currently rampant. Nowadays, many children who are still in school become victims or perpetrators in cases of violence, so that in order not to have a negative impact, it is necessary to educate students in each school. Based on the results of the data, it shows that the P3A Division has successfully entered several schools in Purbalingga Regency to provide education related to violence against children. The implementation of socialization initially goes through a coordination stage, which can be done in two ways, namely by inviting the speaker and coordinating the P3A Division with the school to be the initial stage before the socialization is carried out. With this research through descriptive qualitative methods, it can provide information related to the socialization of violence against children.